Kecakapan Nazhir Dalam Pengelolaan Wakaf Produktif Di Indonesia - Sylvianie, Lulu (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
The potential of waqf in Indonesia for strengthening the recipient's economy is still very large if nazhir manages it productively. Although many regulations related to his existence have been made, the quality of nazhir in Indonesia is far from what has been expected. This research aimed to answer the question of why nazhir still faces a low level of professionalism. The methode used was a library research analyzing 29 data. This research found that there were six most influential factors related to the low quality of nazhir performance in Indonesia: lack of managerial skills, lack of education or training, unprofessional recruitment of nazhir, the traditional paradigm of nazhir, legal status of nazhir, and minimum number of nazhir. In order to strengthen waqf governance, it is suggested that a managerial requirement clause be added in addition to integrative and continuous training for nazirs.